Just Wright [videorecording (DVD)] - Hamri, Sanaa; Queen Latifah, 1970-; Common (Musician); Grier, Pam, 1949-; Patton, Paula; Rashad, Phylicia, 1948- (Twentieth Century Fox Home Entertainment, 2010)
"Leslie Wright (Latifah) is a straight-shooting physical therapist who gets the gig of a lifetime working with injured NBA star Scott McKnight (Common). Leslie not only whips Scott into shape, she helps take his game to the next level and all is going well-- until Leslie finds herself falling for him. Oblivious to her growing affection, Scott only has eyes for Morgan (Paula Patton), Leslie's sexy and seductive friend. With everything on the line, Leslie must take her best shot and find out if she and Scott are just right for each other"--Container.